Technical channel of information leakage by side electromagnetic re-radiation of auxiliary technical means and systems - Zabolotnyi, V.I.; Oleynikov, A.M.; Zabolotnyi, D.M.; Kustov, A.K. (Radiotekhnika, 2024)
The design and implementation of a complex of technical information protection requires the identification and analysis of technical channels of information leakage. The work is devoted to the analysis of the channel of side electromagnetic re-radiation of auxiliary technical means and systems provided by the main technical means. The article presents approaches to the methodological support of the process of creating and applying separate quantitative models of TKVI, which are formed by the processes of the formation of side electromagnetic radiation, their impact on the random antenna of auxiliary technical means and systems, re-radiation of the field outside the controlled zone, their further composition with the radiation field of the main technical tool. Research is based on the theory of the electromagnetic field, current organizational documents in the field of technical information protection practice. Expedient areas of further research arising from related problems, namely the development of quantitative models, have been identified: leakage of information due to the phenomenon of electric induction of the electric component of the field on a random electric antenna; leakage of information due to the reradiation of the electric field component of the electric field antenna created by the OTZ magnetic antenna and vice versa.